Pengaruh Penggunaan Umpan dan Konstruksi Funnel terhadap Hasil Tangkapan Bubu Laut Dalam di Teluk Palabuhanratu - Ari Purbayanto; Adi Susanto; Eddi Husni (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
The main objective of this research was to analyze the influence of bait and funnel constructions on the catch of deep sea pot in Palabuhanratu Bay. The experimental fishing used each of 5 units rigid and soft funnel of the deep sea pots filled with bait of shark and ray meat. The result showed that shark and ray baits did not have a significant influence on the weight of pots catch. The rigid and soft funnel constructions also did not have a significant influence on the catch. Therefore, both shark and ray baits used on the deep sea pots for catching fish at the depth of 200 m in Palabuhanratu Bay had the same effectiveness. The rigid funnel pot was a more suitable construction to catch fish, because it was easy to construct, relatively heavy and fast to sink, so it reduced the setting time.